Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Pengelolaan Keuangan Pribadi Mahasiswa FEB Universitas Kristen Satya Wacana - Pratita, Dinda Oktaviana; Martono, Samuel (Jurnal Samudra Ekonomi dan Bisnis, 2024)
Developments in this era really support changes in human life, for example technological developments which have an impact on the lifestyle of the younger generation. In other words, the younger generation needs to know how to manage finances well. Meanwhile, there are still many young people, especially students, who are mostly not good at managing their finances. This research is therefore needed to determine personal financial management in terms of financial literacy and student financial attitudes. Research questionnaires were distributed to 226 FEB UKSW students class of 2020, then the data was tested using the multiple regression method, with the help of SPSS 23 software. The results of the analysis prove that there is an influence between financial literacy and financial attitudes on personal financial management in students simultaneously.